Hidden Ideologies in Indonesia’s World Water Forum 2024 Speech - Haikal Fadhil Anam; Hilma Erfiani Baroroh (Jurnal ILMU KOMUNIKASI, 2026)
This study analyzes the ecological and ideological dimensions of President Jokowi’s speech at the World Water Forum 2024 using Norman Fairclough’s critical discourse analysis model and Arran Stibbe’s ecolinguistic framework. The findings reveal an interplay of beneficial, ambivalent, and destructive ideologies. The speech emphasizes moral responsibility and global cooperation in water conservation, while also reflecting economic growth and consumerist ideologies that may undermine ecological sustainability. This study highlights the importance of critical evaluation to promote communication and policymaking aligned with ecological and sustainable principles.